ANALISA STUDI TENTANG PERANCANGAN ALAT MONITORING KUALITAS AIR PDAM BERBASIS INTERNET OF THINGS : ANALYSIS STUDY: DESIGN OF LOCAL WATER SUPPLY QUALITY MONITORING USING INTERNET OF THINGS - Anifatul Faricha; Dimas Adiputra; Isa Hafidz; Lora Khaula Amifia; Moch. Iskandar Riansyah (Program Studi Teknologi Informasi, 2019)
Abstract Nowadays, as the gain of the global manufacturing technology, particularly at the industrial revolution 4.0, commonly it has also been increasing the amount of the waste products which directly impact and contaminate to the water quality. Hence, the water monitoring is required to maintain water’s quality whether it is safe or not, moreover at the local water supply utility (PDAM) which generally consumed by residents. Water quality monitoring becomes a vital issue and main concerns in these current days because the numbers of water resources are limited, whereas the total citizens in Indonesia are continuously increasing. Therefore, this study presents a review analysis about the design of water quality monitoring using the Internet of Things (IoT), which includes the key parameters selection at the water quality, proper sensors selection, and also IoT's platforms selection. Water quality monitoring will be acquired at several points in Surabaya using sensor array contain many sensors such as temperature sensors, turbidity sensors, conductivity sensors, and oxygen gas sensors. Then, data acquired from sensors are transmitted to the microcontroller which has the IoT module. Hence, information access from central to the user can be monitored, downloaded, or controlled everywhere and anywhere.